Research on Structural Characteristics of Dynamic Nuclear Zone in Dynamic System of Coal and Rock - Hai Rong; Bing Liang; Hongwei Zhang; Feng Zhu (Advances in Civil Engineering)
In order to calculate the concrete scale range of coal and rock mass in rockburst of different degrees of danger and to prevent and control rockburst in coal mines, the concept of dynamic system of coal and rock is put forward in this paper. The model of the relationship between the occurrence of rockburst and dynamic system is built at the same time, which could be used to analyze the rockburst risk of coal and rock in different scales. The calculation method of dynamic nuclear zone scale and its evaluation system and quantitative indicators are put forward based on the energy release process of dynamic system of coal and rock. Combined with the fracturing technology of liquid CO2, the accuracy of the calculation method for the radius of dynamic nuclear zone is verified in a coal mine in Shanxi Province. The degree of coincidence between the results of the two methods is 96.9%∼97.5%, which shows that the calculation method for the radius of dynamic nuclear zone has high reliability and practicability. This method can be widely used in forecasting the risk of rockburst. The liquid CO2 fracturing method can be well used to simulate the blasting source of rockburst at the same time and can be applied to more mines in the future.